Analisis Kebutuhan Air Dan Evaluasi Pola Tanam Daerah Irigasi Kedung PutriKabupaten Purworejo - PARWATA, Adam Said ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The increasing of food requirements will be directly proportional to the increasing of population. Unfortunately this is not comparable to the increasing of available resources. Agricultural area is decreasing and turned into homes, buildings, factories, roads, etc. The number of potential problems arises due to lack of irrigation water supply especially during the dry season is necessary to make the calculation and analysis of crop water requirements, irrigation water availability, and evaluation of cropping patterns and planting schedule that already exists. The first step was to find out the availability of water at the intake. Then, the water requirement is calculated based on the value of irrigation water requirement for land preparation, potential evapotranspiration, percolation, replacement of the water layer, and the effective rainfall. The comparison of water requirement at the intake and the availability of water analysed using Planting Layout Plan 2013/2014. If there is a period that the water requirment is not fulfilled, it has to be calculated the maximum area that can be planted in one growing season. Based on the availability of water at the intake in October 2011-September 2012 and October 2012-September 2013 with Conventional Method and Water Saving Irrigation method in a row there is a lack of water during the period of 10 and 9 of the 38 periods, only fulfill the water needs of 73.68% and 76, 3% of the total available periods. There is a water shortage in the period of land preparation. The water requirement for land preparation only requires 100 mm is much smaller than the standard KP-01 by 250 mm based on the analysis of real water needs of the harvested area by the availability of water. There is an increase in the maximum area that can be planted with rice by 55.8% to 19% MT I and MT II to save water by using the method compared with conventional methods.